Colima sin Dios, sin ley ni rey: una interpretación - José Miguel Romero (Estudios sobre las Culturas Contemporáneas, 1992)
Colima conquest was -following this text- a fact done by mistake and against all sorts of odds. It this a fluid essay that achives to introduce the reader in history knowledge about Colima. It speakes about interwoven situations of Colima conquest and the foundation of Villa de San Sebastiaan. A posible interpretation is made upon the happenings present in the xvi, based on the motives for the conquest.